The Modified Ghost Fluid Method Applied to Fluid-Elastic Structure Interaction (Advances in Applied Mathematics and Mechanics, 2011)
In this work, the modified ghost fluid method is developed to deal with2D compressible fluid interacting with elastic solid in an Euler-Lagrangecoupled system. In applying the modified Ghost Fluid Method to treat thefluid-elastic solid coupling, the Navier equations for elastic solid arecast into a system similar to the Euler equations but in Lagrangian coordinates.Furthermore, to take into account the influence of material deformation andnonlinear wave interaction at the interface, an Euler-Lagrange Riemann problemis constructed and solved approximately along the normal direction of theinterface to predict the interfacial status and then define the ghost fluidand ghost solid states. Numerical tests are presented to verify the resultantmethod.